The Effectiveness of Real Problem-Based e-LKPD to Improve Problem Solving and Collaboration Abilities on Environmental Change Material in Madrasah Aliyah - Naimatus Sa'diyah; SIgit Saptono (Universitas Negeri Semarang, 2023)
At Madrasah Aliyah Negeri 2 Pati, the subject of Biology, especially the Environmental Change material, has not yet implemented e-LKPD and still uses textbooks from schools. This study aims to analyze the effectiveness of real problem-based e-LKPD to improve students' problem solving and collaboration abilities on environmental change material at Madrasah Aliyah. Data collection in this study was carried out by tests and observations. The type of this research was Quasi Experiment Design which was carried out at MA Negeri 2 Pati with the research population being class X at MA Negeri 2 Pati, the samples for this research were classes X2, X4, X6, and X9. Sampling was done by purposive sampling technique. The results of the study were based on the classical completeness score, the percentage of students who passed was 83.33% in the experimental class and 26.67% in the control class. The Independent Sample t-Test showed that problem solving abilities obtained a value of Sig 0.000 <0.05, meaning that there was an average difference between the posttest scores of the experimental and control classes. The results of the N-Gain Test for the experimental class obtained a value of 0.60 in the medium category and 0.29 in the control class in the low category. The results of the experimental class collaboration ability at each meeting increased and the value was higher than the control class. From the results of the study, it was concluded that e-LKPD based on real problems is effective for improving students' problem solving and collaboration abilities on the material on Environmental Change in Madrasah Aliyah.